Safety incentive program for construction project: case studies of several construction projects in Klang Valley, Malaysia - Abas, Nor Haslinda; Nurahim, Mohammad Hafiz; Yasin, Norazam; Rahmat, Muhamad Hanafi (Horizon Research Publishing Corporation, 2020)
This paper presents a study on the effectiveness of safety incentive programs on construction sites in Klang Valley, Malaysia. Five construction projects that implemented safety incentive program were selected as case studies for this research. Interviews with the safety personnel for each project were conducted. The findings show that all selected case study projects had implemented a safety incentive program in different ways, such as using safety awards, housekeeping, unsafe behavior reporting, etc. However, there were issues and weaknesses in implementing these programs as raised by the respondents, which included miscommunication between the employee and the management, unsatisfactory safety awareness by employees, and so on. Some of the suggestions given by the respondents to minimize these problems included implementing communication courses, promoting programs through security campaigns and management involvement. The findings of this study provide information on the implementation of a safety incentive program at the construction site, and can also be used as a source of reference within the site safety management on how to properly implement the program.